Mechanical response characteristics and damage mechanism of water-containing mudstone under low strain rate dynamic loading - Guichen LI; Sen YANG; Yuantian SUN; Jinghua LI; Haoran HAO; Zeyu SHAO (Meitan xuebao)
Accelerated instability and failure of surrounding water-rich mudstone in roadway under dynamic loading has become a prominent problem in deep coal resource mining, and it is of great significance to study the damage mechanism of water-containing mudstone mass under disturbing loads in depth. A low strain rate dynamic load disturbance test was carried out to analyze the effects of different water content, dynamic load rate and dynamic load intensity factors on the mechanical response characteristics of mudstone. The behavioral characteristics of elastic-plastic deformation during the dynamic load disturbance stage were also elucidated. The distribution characteristics of tensile and shear damage in different loading stages of mudstone were also clarified. The mechanisms of fine-scale structural evolution of mudstones under water-rock and dynamic loading were revealed. The results show that: ① low strain rate dynamic loading still has a weakening effect on the strength of mudstone, the ability of mudstone to resist the disturbance of dynamic loading decreases with the increase of water content, dynamic loading rate, and strength, and the strength damage reaches the maximum of 28.47%, 59.76%, and 31.56%, respectively. ② The acoustic emission characteristic parameter law shows that during the loading process, the mudstone has gone through four fracture evolution stages: initial damage, damage intensification, damage quiescence (exacerbation), and damage development, and the Kaiser effect is more obvious at the lower level of each factor in the dynamic loading perturbation stage, and the Felicity effect is more significant at the higher level of each factor. ③ The loading strain and plastic strain of the mudstone under the initial dynamic load disturbance are the largest, and the time of the second significant damage of the mudstone is advanced at higher levels of each factor. Higher dynamic loading rates and strength tests show a high correlation between loading strain and plastic strain during disturbance, and the plastic strain is always greater than the elastic strain. ④ The percentage of shear damage in the whole loading process of mudstone increases with the increase of water content, in which the dynamic loading stage increases significantly from 6.94% in dry to 33.95% in saturated, and the macroscopic shear damage characteristics are gradually obvious. ⑤ Dissolution and subduction of water in saturated mudstone, fracture of cementation under higher-rate dynamic loading, and wide-scale displacement of particle cementation under higher-intensity dynamic loading are the fundamental causes of the deterioration of mudstone mechanical properties. ⑥ A mudstone damage model considering lateral stress and cyclic dynamic loading was constructed and verified using the stress-strain relationship between loading and unloading during the cyclic dynamic loading stage of specimens with different water contents, and the model parameter F0 has a more significant effect on the strength of mudstone specimens compared with the parameter m. The model is based on the model of mudstone damage, and the model has a more significant effect on the strength of mudstone specimens. The research results provide a scientific basis for revealing the damage mechanism of water-containing mudstone under low strain rate dynamic loading, and helping to deeply understand the accelerated instability problem of surrounding water-rich mudstone in roadway under a dynamic loading disturbance.